Evaluation of Performance, Organ Characteristics and Economic Analysis of Broiler Finisher Fed Dried Rumen Digesta - Esonu, B.O.; Ogbonna, U.D.; Anyanwu, G.A.; Emenalom, O.O.; Uchegbu, M.C.; Etuk, E.B.; Udedibie, A.B.I. (International Journal of Poultry Science, 2006)
A 28-day feeding trial involving 264, 5-week old Hubbard broilers was carried out in a completely randomized design to evaluate the performance, organ characteristics and economic analysis of broilers fed dried rumen digesta (DRD) at dietary levels of 0, 5, 10 and 15% respectively. Feed intake of the groups on varying dietary levels of dried rumen digesta were significantly (P< 0.05) higher than the control (0%) group. Birds on diets containing dried rumen digesta recorded higher body weight gain than the control (0%) group. However, this increase in body weight, feed conversion ratio and relative organ weights were not significant (P>0.05). The lower feed cost per kilogramme meat produced on dried rumen digesta diet suggest that the material is economically viable alternative. Furhter research is necessary to investigate the biosafety of dried rumen digesta.